2013
DOI: 10.1007/s11051-013-1780-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel strontium-doped bioactive glass nanoparticles enhance proliferation and osteogenic differentiation of human bone marrow stromal cells

Abstract: The present study investigates a new family of bioactive glass nanoparticles with and without Sr-doping focusing on the influence of the nanoparticles on human bone marrow stromal cells (hBMSCs) in vitro. The bioactive glass nanoparticles were fabricated by flame spray synthesis and a particle diameter of 30-35 nm was achieved. Glass nanoparticles were undoped (BG 13-93-0Sr) or doped with 5 wt% strontium (Sr) ) and used at concentrations of 10 and 100 g/cm² (particles per culture plate area), respectively. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
1
26
0
1
Order By: Relevance
“…More recently, Strobel et al . () reported the increased expression of Bglap , Col1a1 and Runx2 in human MSCs after 14 days of exposure to cell culture medium containing nanoparticles of strontium‐substituted bioactive glass fabricated by flame spray synthesis. However, the bioactive glass content was regularly renewed throughout the experiment, as opposed to what was done in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Strobel et al . () reported the increased expression of Bglap , Col1a1 and Runx2 in human MSCs after 14 days of exposure to cell culture medium containing nanoparticles of strontium‐substituted bioactive glass fabricated by flame spray synthesis. However, the bioactive glass content was regularly renewed throughout the experiment, as opposed to what was done in this study.…”
Section: Discussionmentioning
confidence: 99%
“…() in the study of mesoporous bioactive glass, by Strobel et al . () in the study of bioactive glass nanoparticles fabricated by flame spray synthesis, and by Zhu et al . () in the study of strontium‐substituted borate bioactive glass compositions.…”
Section: Introductionmentioning
confidence: 96%
“…The compositions of the nBG were very close to i) 45S5 composition (47.8 wt% SiO2, 25.1 wt% CaO, 22.6 wt% Na2O, 4.6 wt% P2O5) [20], ii) 13-93 BG (53 wt.% SiO2, 20 wt.% CaO, 6 wt.% Na2O, 4 wt.% P2O5, 12 wt.% K2O, 5 wt.% MgO ) and iii) 13-93-5Sr (mean particle size 30-35 nm) composition (53 wt.% SiO2, 15 wt.% CaO, 6 wt.% Na2O, 4 wt.% P2O5, 12 wt.% K2O, 5 wt.% MgO, 5 wt.% SrO). These glass nano powders were fabricated by the flame spray method [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Strobel et al assessed the osteogenic potential of BGNPs containing strontium (SiO 2 -CaO-P 2 O 5 -Na 2 O-K 2 O-MgO-SrO) on human bone marrow stromal cells (hBMSCs). 80 Cell growth and morphology studies showed the high cytocompatibility of the nanoparticulate bioactive glass. Moreover, the strontium-doped particles improved the expression of osteocalcin, collagen type I and vascular endothelial growth factor.…”
Section: Physiochemical Properties and Biological Implicationsmentioning
confidence: 99%
“…Moreover, the strontium-doped particles improved the expression of osteocalcin, collagen type I and vascular endothelial growth factor. 80 However, is also important to notice that increasing their strontium content can delay the bioactive behavior of BGNPs because of the inhibitory effect of strontium on apatite mineralization. 81 Xue et al synthesized monodispersed europium (Eu)-doped BGNPs with a dual function of bioactivity and luminescence by a template-assisted sol-gel method.…”
Section: Physiochemical Properties and Biological Implicationsmentioning
confidence: 99%